Introducer director: A new tool to extract the introducer from the contralateral chest during Nuss procedure - Sunghoon Kim; Barnard Palmer; Olajire Idowu (Elsevier, 2023)
One of the technical difficulties encountered during a Nuss procedure is the extraction of the Introducer instrument once it has crossed the anterior mediastinum. Sometimes, this maneuver is done with brute force and without precision. Therefore, a creation of a surgical tool to facilitate precise extraction of the Introducer would benefit the surgeon and optimize the surgical result. Introducer Director (ID) is made of curved steel with a hollow tip and a handle. It has a curved tip appearance like the Introducer. Once the Introducer has traversed the anterior mediastinum, another Introducer is used to enter the contralateral chest at the desired exit site on the chest. Contralateral Introducer is withdrawn and replaced with the ID. A videoscope is used to visualize the joining of the two instruments. While keeping the two instruments mated by applying opposing forces, the Introducer is pushed with a greater force to exit the contralateral chest following the tract created by the ID. ID facilitates the Introducer to exit the contralateral chest at the precise location with ease. Guess work or brute force is no longer needed.